Приключения Васи Куролесова: [повесть: для среднего школьного возраста: 12+] / Юрий Коваль : [худ. А. Шахгелдян] - Коваль Юрий Иосифович (Внеклассное чтение, 2013)
Экземпляры: ФО-14 (20131126) / Инвентарный номер: 48701 / Цена: 67.65 / Сис.шифр: Р2ср / Авт.знак: К 56 / ГРНТИ: 17.82.93 / ББК: 84(2Рос.Рус)6